Representation Analysis of Science Process Skills With a Neuropsycological View at Elementary School - Novaria Lailatul Jannah; Mochamad Nursalim; Sujarwanto Sujarwanto (EDUTEC : Journal of Education And Technology, 2022)
This study aims to analyze how the representation of science process skills in science learning tools from a neuropsychological perspective uses tools that are valid, practical, and also effective in training science process skills which will later produce an image or representation of science process skills. This study uses three stages of the 4-D model, with the stages of definition, design, and development. This research is only limited to development. The representation of the learning device was tested in the fifth grade of elementary school with a one group pretest-posttest design. The results showed that the representation of science process skills was interesting and easy to understand. By showing learning practicality data, device validity data, and also device effectiveness data in representing science process skills. Assisted by a very positive student response, it shows that the neuropsychology of students looks good. Overall, the representation of science process skills using this learning tool can help students process thinking more logically, and balance behavior better.